Formal Professionalization of early-stage Social Media "Influencers"—attitudinal Drivers and Their Relation to Personality Traits. Issue 3 (3rd July 2022) - Kolo, Castulus; Haumer, Florian; Roth, Alexander
ABSTRACT: By seeking relationships with advertisers, actively posting social media users become "influencers" in the sense of influencer marketing. As such, they combine content based on personal stories or specific capabilities with third parties' commercial interests. Unlike research on well-known social media celebrities, in this study we focus on nascent media professionals in the early stages of developing from co-consumers to having their first financial success. We conducted a survey of 3500 such "nano" to "micro" influencers from a leading agency's German database to identify the principal components of attitudes that extant research proposes as drivers of formal professionalization. To achieve this, we operationalized and adapted theoretical concepts to influencers as a new kind of content creator. Characteristically, professionalization paralleled by reach is driven by a combination of established scales on entrepreneurial orientation, manifest in "proactiveness" and "risk-taking, " as well as a brand orientation, resulting from "market mavenism" and "brand engagement in self-concept." However, a structural equation model not only suggests that there are additional drivers but also links the identified drivers to personality traits based on the five-factor OCEAN model. Hence, becoming an influencer is to some extent catalyzed by socialization; it requires the ability and willingness to entice an increasingly large followership with unique content, which represents both a challenge and an inspiration for incumbent media organizations.